2017
DOI: 10.3329/jbau.v15i1.33527
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characters of oilseeds from selected mustard genotypes

Abstract: To evaluate the physicochemical characteristics of oilseeds, three varieties of mustard oilseeds were studied their seed weight, moisture, ash, carbohydrate, protein, fat, total energy and minerals composition of oil and cake. Among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
3
6
1
Order By: Relevance
“…Fe was the most abundant of the analyzed oligoelements in all seeds, ranging from 2.34 µg/g in C. adamantinus to ten-fold more (25.6 µg/g) in B. harleyi. These values are lower than those described for mustard seeds (75-170 µg/g) [29], but the Fe level in B. harleyi is comparable to the values found in the literature for some well-known edible nuts such as pecan nuts (24-26 µg/g) and peanuts (20 µg/g) [28], and to the tropical babassu (Orbignya speciosa) nuts (18-33 µg/g) and sapucaia (Lecythis pisonis) nuts (21-36 µg/g) [14]. H. volubilis and C. guianensis oilseeds contained similar Fe concentrations to those reported for cupuassu (Theobroma grandiflorum) seeds (7.5 µg/g) [14].…”
Section: Diplopterys Pubipetalacontrasting
confidence: 72%
See 1 more Smart Citation
“…Fe was the most abundant of the analyzed oligoelements in all seeds, ranging from 2.34 µg/g in C. adamantinus to ten-fold more (25.6 µg/g) in B. harleyi. These values are lower than those described for mustard seeds (75-170 µg/g) [29], but the Fe level in B. harleyi is comparable to the values found in the literature for some well-known edible nuts such as pecan nuts (24-26 µg/g) and peanuts (20 µg/g) [28], and to the tropical babassu (Orbignya speciosa) nuts (18-33 µg/g) and sapucaia (Lecythis pisonis) nuts (21-36 µg/g) [14]. H. volubilis and C. guianensis oilseeds contained similar Fe concentrations to those reported for cupuassu (Theobroma grandiflorum) seeds (7.5 µg/g) [14].…”
Section: Diplopterys Pubipetalacontrasting
confidence: 72%
“…The Mg contents in the samples (362 to 586 µg/g) were very modest compared to the levels found for some common culinary nuts and seeds (almonds (~2000 µg/g), pecans (~1500 µg/g), hazelnuts (2000 µg/g) [28], and mustard oilseeds (~7000 µg/g) [29].…”
Section: Diplopterys Pubipetalamentioning
confidence: 61%
“…The total mean carbohydrate value of five malting barley varieties analyzed in this study was 76.84%, slightly higher than 75% of total carbohydrate reported by other authors [3]. Malting barley seeds have significant amounts of carbohydrates (Figure 1), mainly starch [23] in comparison with fruit seeds such as melon which contains 7.22% [24], oilseeds such as mustard with 16.29% [25] and legumes which in general contain 60% carbohydrates [26]. Protein content in malting barley seeds revealed that the Esmeralda variety had the highest value (13.29%), followed by Esperanza (12.77%), Armida (12.53%), Alina (12.48%), and Adabella (11.30%).…”
Section: Resultsmentioning
confidence: 47%
“…The oil extracted by cold press represents the highest proportion of the oil. In the literature, Sharif et al [9] did the comparative analysis of three varieties of specific mustard genotypes which were BARI Sarisha-15, BARI Sarisha-16, and BARI Sarisha-17 in which it was observed that BARI Sarisha-17 contain more oil (41.98%), than BARI Sarisha-16 (40.95%) and BARI Sarisha-15 (41.85%). In another study, Verma et al [10] The FFA value is considered as an important qualitative parameter in the food industry.…”
Section: Resultsmentioning
confidence: 99%